2022
DOI: 10.1080/14756366.2022.2121393
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity carbonic anhydrase inhibitors: challenges and opportunities

Abstract: The mitochondrial isoforms VA/VB of metalloenzyme carbonic anhydrase (CA, EC 4.2.1.1) are involved in metabolic processes, such as de novo lipogenesis and fatty acid biosynthesis. We review the drug design landscape for obtaining CA VA/VB-selective/effective inhibitors, starting from the clinical observations that CA inhibitory drugs, such as the antiepileptics topiramate and zonisamide, or the diuretic acetazolamide induce a significant weight loss. The main approaches for designing suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Based on these clinical findings, ABAT suppression by vigabatrin does not seem to be a promising target for reducing antipsychotic-induced weight gain and metabolic complications originating from hypothalamic AMPK signalling activation. On the other hand, mitochondrial carbonic topiramate and zonisamide have been reported to be effective against antipsychotic-induced weight gain 74 . Unfortunately, these two antiepileptic drugs are inappropriate for patients with epilepsy and comorbid psychotic symptoms and mood disorders 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these clinical findings, ABAT suppression by vigabatrin does not seem to be a promising target for reducing antipsychotic-induced weight gain and metabolic complications originating from hypothalamic AMPK signalling activation. On the other hand, mitochondrial carbonic topiramate and zonisamide have been reported to be effective against antipsychotic-induced weight gain 74 . Unfortunately, these two antiepileptic drugs are inappropriate for patients with epilepsy and comorbid psychotic symptoms and mood disorders 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition studies on CA VA and CA VB. Mitochondrial human CA VA is unique owing to its role in several biosynthetic reactions, and it has been shown that CA VA is a potential target for the design of anti-obesity agents (Supuran, 2022). Although it is extremely difficult to design CA isoform-specific inhibitors owing to the very high similarity of the active sites (Alterio et al, 2012;Pinard et al, 2015), it is important to design inhibitors with minimal affinity to other CAs to avoid non-specific effects.…”
Section: Figure 3 Alignment Of the Human Carbonic Anhydrase Va And Vb...mentioning
confidence: 99%
“…For these reasons, the different CA isoforms have emerged as attractive targets for therapeutic intervention and many efforts were made in the design of novel and effective carbonic anhydrase inhibitors (CAIs). To date, CA inhibition has been shown to have therapeutic potential in the treatment of a wide range of diseases, including edema, glaucoma, epilepsy, obesity, neuropathic pain, and cancer [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%